Didactic strategies to improve the reading skills in 8th grade students at escuela de educacion basica particular universidad católica from universidad católica Santiago de Guayaquil - Morales García, Mónica Raquel (2018)
English is the second language most spoken in the world, therefore is a foreign language used in schools, high schools, colleges and thanks to new learning methods that foster students an important role in educationsystem. For a student learning the Spanish language can be easy, but to learn a new foreign language can be a complicated experience if they do not have a good preparation………